The literary Cold War, 1945-Vietnam - Piette, Adam (Edinburgh University Press, 2009)
This is a ground-breaking study of the psychological and cultural impact of the Cold War on the imaginations of citizens in the UK and US. The Literary Cold War examines writers working at the hazy borders between aesthetic project and political allegory, with specific attention being paid to Vladimir Nabokov and Graham Greene as Cold War writers. The book looks at the special relationship as a form of paranoid plotline governing key Anglo-American texts from Storm Jameson to Sylvia Plath and Ted Hughes, as well as examining the figure of the non-aligned neutral observer caught up in the sacrificial triangles structuring cold war fantasy. The book aims to consolidate and define a new emergent field in literary studies, the literary Cold War, following the lead of prominent historians of the period. Key Features One of the first influential monographs to look at leading Anglo-American writers 1945-Vietnam in terms of the Cold War as psychological and fantasy phenomenon Exemplary form of literary criticism combining close reading and new historical forms of research Significant readings of key postwar writers, including Sylvia Plath, Ted Hughes, Mary McCarthy, Graham Greene and Vladimir Nabokov A major contribution to twentieth-century war studies, especially with its focus on the special relationship between the US and the UK, of obvious political and cultural relevance today